2017
DOI: 10.4103/sni.sni_137_17
|View full text |Cite
|
Sign up to set email alerts
|

Fatal cerebral swelling immediately after cranioplasty: A case report

Abstract: Background:Cranioplasty is a standard neurosurgical procedure which is performed after decompressive craniotomy. Fatal complications associated with this procedure are not well documented. Here, we report a case of fatal cerebral swelling after cranioplasty and discuss the possible mechanism of this complication.Case Description:A 64-year-old man was admitted with the diagnosis of cerebral hemorrhage, and emergency surgery for hemorrhage removal and decompressive craniotomy were performed. One month after surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…[ 26 ] In his treatise, Dieulafoy cautioned that “the operator must be condemned who makes use of aspiration without understanding.”[ 26 27 ] The induction of acute intracranial hypotension by subgaleal drains can result in catastrophic outcomes. [ 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 28 32 ] Our patient likely experienced ATH when vacuum suction to the supratentorial compartment was applied. The immediate clamping of the subgaleal drain with subsequent recovery of the patient's consciousness and stabilization of vital signs supports this theory.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…[ 26 ] In his treatise, Dieulafoy cautioned that “the operator must be condemned who makes use of aspiration without understanding.”[ 26 27 ] The induction of acute intracranial hypotension by subgaleal drains can result in catastrophic outcomes. [ 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 28 32 ] Our patient likely experienced ATH when vacuum suction to the supratentorial compartment was applied. The immediate clamping of the subgaleal drain with subsequent recovery of the patient's consciousness and stabilization of vital signs supports this theory.…”
Section: Discussionmentioning
confidence: 97%
“…Sviri [22] can result in catastrophic outcomes. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]28,32] Our patient likely experienced ATH when vacuum suction to the supratentorial compartment was applied. The immediate clamping of the subgaleal drain with subsequent recovery of the patient's consciousness and stabilization of vital signs supports this theory.…”
Section: Outcomementioning
confidence: 99%
“…Sviri et al reported four patients (young males who underwent decompressive craniectomy after TBI) who died soon after cranioplasty due to massive cerebral swelling, possibly due to negative pressure differences in the brain causing massive shift toward the cranioplasty site and a fatal vasomotor reaction 1,2 . The elimination of atmospheric pressure causes negative pressure on the brain, and the use of a closed subgaleal suction drain exacerbates this pressure change, leading to secondary ischemia and brain swelling 2,6 . As described in Sviri et al and Honeybul et al, sinking skin flap syndrome (SSFS) may occur if the brain gravity and atmospheric pressure exceeds the ICP and produces a cavity when the craniectomy is performed.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 The elimination of atmospheric pressure causes negative pressure on the brain, and the use of a closed subgaleal suction drain exacerbates this pressure change, leading to secondary ischemia and brain swelling. 2,6 As described in Sviri et al and Honeybul et al, sinking skin flap syndrome (SSFS) may occur if the brain gravity and atmospheric pressure exceeds the ICP and produces a cavity when the craniectomy is performed. The large cavity between the heavily collapsed brain and plate is filled by the collapsed brain, resulting in rapid hemodynamic pressure changes.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that a sudden increase in ICP that hits on a brain chronically exposed to intracranial hypotension has a main role in causing a sequence of pathologic changes after cranioplasty. [13][14][15] Overdrainage by using a vacuum suction drain may cause postoperative venous congestion and stasis, leading to malignant cerebral swelling. Shen et al 13 reported that their patient exhibited dilated and fixed pupils after a vacuum suction drain had drained 300 mL CSF.…”
Section: Discussionmentioning
confidence: 99%